Pelatihan Pengembangan Bahan Ajar Berbasis Flip Pdf Profesional Berbantuan Matlab Untuk Mendukung Pembelajaran P5 - Purwaningsih, Sri; Riantoni, Cicyn; Pathoni, Haerul; Nurhatmi, Jules; Hendri, Menza (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of the Strengthening Pancasila Student Profile (P5) projects requires learning resources that are easy to adopt, engaging, and supportive of authentic assessment; however, in practice there are still constraints related to teachers’ ICT literacy, software availability, and the scarcity of ready-to-replicate examples. This training addressed these issues through an integrated package—guidelines and templates for Flip PDF Professional, access to MATLAB/software, and an online mentoring forum—with the following objectives: to train teachers to design digital learning materials using Flip PDF integrated with MATLAB for P5 projects; to enhance teachers’ understanding of technology use in strengthening the Pancasila Student Profile; and to help teachers produce interactive, data-driven, problem-solving-oriented learning resources. The program involved 14 teachers and proceeded in five stages: preparation–agreement, needs identification, Technical Training I (Flip PDF), Technical Training II (MATLAB & P5 integration), and formative–summative evaluation. All participants produced P5 flipbook prototypes featuring multimedia, clear navigation, and reflection pages; most embedded charts/tables generated in MATLAB. Likert-scale questionnaire results indicated positive perceptions (mean 4.40; Cronbach’s α = 0.864), with strengths in facilitation & outputs (4.64), P5 relevance (4.57), sustainability (4.50), and Flip PDF ease of use (4.43). The area requiring further strengthening was MATLAB integration (3.86), which was followed up through technical clinics, dataset templates, and guidance on numeric locale settings. These findings confirm the effectiveness and replicability of this training model in P5 contexts.